1993
DOI: 10.1016/0014-5793(93)80106-5
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus is one of the heterogeneous phenotypic features of a mitochondrial DNA point mutation within the tRNALeu(UUR) gene

Abstract: A heteroplasmic point mutation (transition A-to-G at nucleotide position 3,243 in the mitochondrial tRNALe"(""a) gene) is found in a family suffering from a syndrome with diabetes, deafness and cardiomyopathy as the predominant clinical features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The phenotypic expression in individuals with deletions and mutations in mitochondrial DNA is highly variable, but includes various combinations of diabetes mellitus [Gerbitz et al, 1993;Goto et al, 1991;Moares et al, 1989;Pilz et al, 1994], hypoparathyroidism [Zupanc et al, 1991], retinal degeneration [Howell et al, 1991;Huoponen et al, 1991;Johns and Smith et al, 1993;Johns and Heher et al, 1993], deafness [Gerbitz et al, 1993;Goto et al, 1991;Moares et al, 1989;Pilz et al, 1989], renal disease [Majander et al, 1991;Superti-Furga et al, 1993;Venkataraman et al, 1987;Zupanc et al, 1991], and mental retardation [Newman et al, 1991;Tatuch et al, 1992]. Accordingly, we isolated DNA and looked for deletions and mutations of the mitochondrial genome.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The phenotypic expression in individuals with deletions and mutations in mitochondrial DNA is highly variable, but includes various combinations of diabetes mellitus [Gerbitz et al, 1993;Goto et al, 1991;Moares et al, 1989;Pilz et al, 1994], hypoparathyroidism [Zupanc et al, 1991], retinal degeneration [Howell et al, 1991;Huoponen et al, 1991;Johns and Smith et al, 1993;Johns and Heher et al, 1993], deafness [Gerbitz et al, 1993;Goto et al, 1991;Moares et al, 1989;Pilz et al, 1989], renal disease [Majander et al, 1991;Superti-Furga et al, 1993;Venkataraman et al, 1987;Zupanc et al, 1991], and mental retardation [Newman et al, 1991;Tatuch et al, 1992]. Accordingly, we isolated DNA and looked for deletions and mutations of the mitochondrial genome.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The reason for the different results may be in the selection of patients, the difference in races, the use of different methods, and the degree of heteroplasmy. The degree of heteroplasmy reported differs in various tissues and in various subjects (15,16,26). Larsson et al (25) reported that Ͼ92% of mtDNA with the tRNA Lys 8344 mutation in muscle is needed to cause respiratory chain dysfunction detected by biochemical methods, and the levels of mutated mtDNA in lymphocytes were 12.0 to 27.6% of those in muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episode [A to G transition mutation in the mitochondrial transfer RNA Leu (tRNA Leu ) gene at position 3243] (14,15), myoclonic epilepsy with ragged red fiber (A to G transition mutation in the mitochondrial tRNA Lys gene at position 8344) (16), and other mitochondrial cytopathies are associated with diabetes mellitus. The above observations suggest that alterations of mitochondrial DNA (mtDNA) may to some degree contribute to the development of diabetes mellitus.…”
mentioning
confidence: 99%
“…This substitution cosegregated with diabetes mellitus and deafness (6,(14)(15)(16)(17)(18)(19) and other clinical manifestations including cardiomyopathy (20) and MELAS (10,21,22). In agreement with a mitochondrial gene mutation, these phenotypes appear to be maternally inherited as shown in Families 1, 3 and 4.…”
Section: Discussionmentioning
confidence: 99%